THE DEVELOPMENT OF CHILDREN’S STRATEGIES. A STUDY OF THE ADDITIVE AND MULTIPLICATIVE REASONING - Rodríguez, Purificación; Lago, María Oliva; Caballero, Sonia; Dopico, Cristina; Jiménez, Laura; Solbes, Irene (Anales de Psicología / Annals of Psychology, 2008)
Young children posses a wide range of arithmetical abilities that enable them to successfully face word problem, with additive and multiplicative structures. To test this, we have assessed the participants twice (i.e., when they were 4 to 5 years old and when they were 5 to 6 years old) with Change and Equal Groups problems, where objects were available to ease the representation of the quantities of the problems. The result showed that: (1) the level of children’s success was very high, regardless the moment of assessment and the kind of problem; (2) only the subtraction problems registered a decrease during the second assessment; (3) the procedures of resolution were mainly based on the direct representation of the quantities for all kind of problems; (4) the counting strategies were used only in the additive and subtractive problems, while the derived fact strategies were mainly applied in the multiplication and division problems; (5) the variability in the use of the strategies was affected by the kind of operation involved in the problem and the moment of the assessment; and finally (6) strategy change seemed to be gradual rather than abrupt.